(untitled) (Comprehensive Journal of Science, 2025)
This study was conducted in the Al-Maraziq area, approximately 30.6 km from Tripoli, during the autumn season. It aimed to compare subsurface drip irrigation (SDI) and surface drip irrigation (DI) systems in terms of water use efficiency and their impact on the growth and yield of potato plants (Spunta). A experimental design with three replications was used. The results demonstrated the superiority of the SDI system in saving irrigation water, conserving about 213 m³/ha (5.4% decrease) compared to the DI system. This is attributed to reduced losses from soil surface evaporation and increased efficiency in delivering water directly to the root zone. The SDI system also achieved higher water productivity of 7.005 kg/m³ compared to 6.492 kg/m³ for the DI system (an increase of 7.9%), indicating a greater crop yield per unit of water consumed. Furthermore, water use efficiency increased to 27.9% under SDI compared to 25% under DI , which positively reflected on the total potato yield, improving it by 550 kg/ha. Statistical analysis showed significant differences (P ≤ 0.05) between the two irrigation systems for most of the studied variables. This superiority can be attributed to the reduction of water stress on the plants and the better distribution of moisture and nutrients in the SDI system. It is considered more effective in enhancing fertilizer uptake, as fertilizers are not lost to evaporation or surface runoff, thus maintaining their concentration around the roots and consequently increasing yield and economic return. These results confirm the superiority of the subsurface drip irrigation system for the effective management of water resources, making it a sustainable option for enhancing potato productivity in arid and semi-arid regions.